Determinants of short birth interval among child-bearing age women in the Gedeb Hasasa district of the West Arsi zone, Ethiopia - Yosef, Tewodros; Debela, Degfachew; Shifera, Nigusie (Frontiers in Medicine, 2023)
Background: Short birth intervals have been linked to higher rates of fetal loss, prenatal mortality, and poorer child survival. Therefore, for nations like Ethiopia with a population policy intended to reduce fertility, understanding the level and factors influencing birth spacing is crucial in order to apply appropriate intervention. This study aimed to assess the prevalence and determinants of short birth interval among child bearing age women in the Gedeb Hasasa district of the West Arsi zone, Ethiopia. Methods: A community-based cross-sectional study was conducted from July 20 to August 20, 2018. A multistage sampling method was used. Face-to-face interview was used to gather data. The collected data were entered into Epi Data version 3.1 then exported to SPSS version 21 for analysis. Logistic regression was used to identify factors associated with short birth interval. The level of significance was declared at a p-value < 0.05. Results: A total of 714 women took part, with a 98% response rate. The median birth interval length was 32 months. The prevalence of short birth interval was 50.4%. After adjusting for confounding variables, being rural resident (AOR=2.50, 95% CI (1.52, 4.09)), having illiterate husband (AOR=4.14, 95% CI (2.15, 8.45)), breastfeeding duration for 7-12 months (AOR=3.16, 95% CI (1.95, 5.13)) and 13-23 months (AOR=2.45, 95% CI (1.52, 3.95)), sex of the prior child (AOR=0.63, 95% CI (0.45, 0.88)), and previous child alive (AOR=0.20, 95% CI (0.14, 0.96)) were the determinants of short birth interval. Conclusion and Recommendation: One in every two women was practiced short birth intervals. The median birth interval duration was 32 months, which is below the minimum standard recommended by WHO duration of the birth interval, which is 33 months. Short birth intervals were determined independently by residence, husband education, breastfeeding time, previous child's sex, and previous child's survival. Therefore, increasing women’s awareness ideal birth interval should be done through community health professionals and health developmental armies.